Ruu Ketahanan Keluarga: Modifikasi Hukum Sebagai Upaya Mencapai Tujuan Hukum Islam Dalam Memelihara Keturunan - Muthmainnah, Muthmainnah (Journal of Islamic Law Studies, 2018)
One of the aims of Islamic Law based on Abu Ishaq Al-Shatibi is to protect ancestry which becomes a very essential aim for human being. On the other side, this aim faces obstacles in which a family does not show the function as it is in society. This writing elaborates a Draft Law which is initiated by Prosperous and Justice Party Faction which was legalised as Draft Law initiated by House of Representatives Republic of Indonesia term 2015-2019. The Draft Law is about Family Sustainability. The process of Law Making is a fundamental aspect for Indonesia as a Rechstaat. This article is needed to cretae a fundamental design for family sustainability. The urgency derives both from sociology aspect and also physchology aspect. The sociology discusses about relations between an individu with the societ while the physchology discusses and individu related to the interaction, emotion, and also performance. This writing also discusses about law modification regarding this article with the paradigm that a family issue becomes a general issue in public law. The existing of this regulation is hoped to achieve one of the aims of Islamic Law which is to protect ancestry.